Analytical Model of Three-Dimensional Ultrasonic Beam Interaction with an Immersed Plate - SOUCRATI, Hanane; CHITNALAH, Ahmed; AOUZALE, Noureddine; JAKJOUD, Hicham (Archives of Acoustics, 2018)
This paper proposes an analytical model to describe the interaction of a bounded ultrasonic beam with an immersed plate. This model, based on the Gaussian beams decomposition, takes into account multiple reflections into the plate. It allows predicting three-dimensional spatial distributions of both transmitted and reflected fields. Thereby, it makes it easy to calculate the average pressure over the receiver’s area taking into account diffraction losses. So the acoustical parameters of the plate can be determined more accurately. A Green’s function for the interaction of an ultrasonic beam with the plate is derived. The obtained results are compared to those given by the angular spectrum approach. A good agreement is seen showing the validity of the proposed model.